THE EFFECT OF THE USE OF CHICKEN MANURE ON RED BEANS (Phaseolus vulgaris L.) - Goo, Alince; Satiman, Utari; Lawalata, Helen; Tumbel, Ferny Margo; Wantania, Johanna (Indonesian Biodiversity Journal, 2025)
Red beans are a horticultural crop belonging to the annual legume group that grows upright and has a fairly high nutritional content. To obtain maximum growth and yield from red beans, several factors must be considered, including balanced fertilizer application. The factor of providing organic fertilizer from chicken manure with the right dosage is the target of this study. This study aims to determine the effect of red bean growth on the dosage of chicken manure fertilizer. This study was conducted from December 2024 to February 2025 and was carried out on the plantation land of the Department of Science Education, Faculty of Mathematics, Natural Sciences and Earth Sciences, Manado State University. The method used is a quantitative method with a type of experiment in the form of a Randomized Block Design (RAK) with five treatment combinations with each repeated three times. A0 = 0 (control), A1 = 1.00 kg, A2 = 1.50 kg, A3 = 2.00 kg, A4 = 2.50 kg, so there are 15 experimental bed units, and the data obtained are then analyzed using analysis of variance (ANOVA). The results of this study indicate that good plant height growth, number of leaves and stem diameter are found in treatment A1 with a dose of 1.00 kg of chicken manure fertilizer and A2 with a dose of 1.50 kg of chicken manure fertilizer because there is the most maximum growth.